H2S‐Activated Ion‐Interference Therapy: A Novel Tumor Targeted Therapy Based on Copper‐Overload‐Mediated Cuproptosis and Pyroptosis - Zhao, Fan; Liang, Liying; Wang, Heng; Wang, Chen; Su, Dan; Yao, Ying; Li, Wangchang; Li, Juan; Zheng, Jingwu; Qiao, Liang; Mou, Xiaozhou; Che, Shenglei; et al. (Advanced functional materials, 2023)
Copper overload is a novel way to achieve copper‐ion‐interference therapy by disrupting copper homeostasis and treating diseases through multiple cell death pathways. However, it is difficult to reach copper overload since excess intracellular copper ions will be pumped out. Herein, copper overload is achieved by both raising cellular uptake and reducing the efflux of copper ions using hydrogen sulfide (H2S)‐responsive copper hydroxyphosphate nanoparticles (Cu2(PO4)(OH) NPs). After immersion in an H2S‐enriched colon cancer microenvironment, Cu2(PO4)(OH) NPs can transform into copper sulfide NPs with reduced size for higher cell entering, resulting in improved Fenton activity as well as copper ion dissociation. Reactive oxygen species generated by the Fenton reaction not only activate inflammasomes and Caspase‐1 proteins, cause the cleavage of gasdermin D to induce pyroptosis, but also affect mitochondrial function and down‐regulate copper exporter ATP7A to further reduce the copper excretion. The combination of higher endocytosis and lower exportation leads to maximized copper overload. Together with the efficient copper ions release, mitochondrial tricarboxylic acid cycle can be disrupted and iron‐sulfur cluster proteins are downregulated, ultimately triggering cuproptosis. As both pyroptosis and cuproptosis are efficient ways to induce cell death, this study provides a novel way to realize effective tumor‐targeted therapy based on H2S‐activated copper overload with simple Cu2(PO4)(OH) NPs.